Income-Based Economic Determinants of Life Expectancy in Four Groups of Countries Classified by their Levels of Income - Ismael Abdulrahman; Sarah Ahmed Chawsheen (Scientific Annals of Economics and Business)
This study seeks to determine the role of per capita value added in the main sectors of; agriculture, industry, services, plus per capita GDP, on life expectancy at birth in the four groups of countries classified internationally by; high income, upper middle income, lower middle income, and low-income countries, during the period 1990-2022. Panel data analysis adopted for each group countries, where CS-ARDL approach is used to measure the effect of the independent variables (sector’s value-added per capita income) on the dependent variable (life expectancy at birth). The findings indicate that the per capita values provided by the sectors of industry and services are important factors in increasing life expectancy in high-income countries. Whereas, increases in per capita GDP would significantly extend life expectancy in countries ranging from upper-middle to lower-middle and low-incomes.